A double substitution induced Ca(Mg0.8, Al0.2)(Si1.8, Al0.2)O6:Eu2+ phosphor for w-LEDs: synthesis, structure, and luminescence properties. Issue 29 (7th August 2015) - Li, Yang; Liu, Wenjing; Wang, Xicheng; Zhu, Ge; Wang, Chuang; Wang, Yuhua
<x xml:space="preserve">Abstract</x> A double substitution induced blue-emitting phosphor Ca(Mg0.8, Al0.2)(Si1.8, Al0.2)O6:Eu2+ (CMAS:Eu2+) was successfully synthesized by a solid-state reaction process, and its structure and luminescence properties were investigated in detail.